UMP-Alcon working together to develop innovative contact lenses - UMP, PNC (2019)
Johor Bahru, March 26 – Universiti Malaysia Pahang (UMP) signed a corporate agreement with CIBA Vision Johor Sdn. Bhd known as Alcon Johor that will build technical depth for business sustainability. This paves the way for research and development activities as well as industrial training placements and exchange programme for university staff and students.